ОПТИМАЛЬНОЕ УПРАВЛЕНИЕ РАСПРЕДЕЛЕНИЕМ ВОДЫ В МАГИСТРАЛЬНЫХ КАНАЛАХ ИРРИГАЦИОННЫХ СИСТЕМ - Рахимов, Ш.Х.; Сейтов, А.Ж.; Кудайбергенов, А.А. (SCIENCE and SOCIETY, 2020)
In the work mathematical models of optimum water distribution in channels of irrigation systems under the conditions of discrete water supply to consumers have been developed. These include the models of direct wave, kinematical wave, convectional and diffusive model, as well as complete model of unsteady water flow in channel sections, that takes into account all main hydraulic characteristics of the channel section.